Fluorescent and colorimetric ion probes based on conjugated oligopyrroles. (7th March 2015) - Ding, Yubin; Tang, Yunyu; Zhu, Weihong; Xie, Yongshu
<x xml:space="preserve">Abstract</x> In this tutorial review, the design strategies, syntheses, and ion sensing properties of conjugated oligopyrroles are described.